The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/1758-2229.12790
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions associated with ammonia‐oxidizing bacteria abundance in fields of switchgrass with and without intercropped alfalfa

Abstract: Summary The nitrogen (N) fertilizer required to supply a bioenergy industry with sufficient feedstocks is associated with adverse environmental impacts, including loss of oxidized reactive nitrogen through leaching and the production of the greenhouse gas nitrous oxide (N2O). We examined effects on crop yield, N fate and the response of ammonia‐oxidizing bacteria (AOB) and ammonia‐oxidizing archaea (AOA) to conventional fertilizer application or intercropping with N‐fixing alfalfa, for N delivery to switchgras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 50 publications
1
13
1
Order By: Relevance
“…Reactive ammonium fertilizer not assimilated by crops or soil microbes can be a major source of N 2 O emissions as a byproduct of ammonia oxidation carried out by ammonia‐oxidizing archaea (AOA) and ammonia‐oxidizing bacteria (AOB) among other abiotic and biotic processes (Sanford et al ., 2012). Due to the vast spatial heterogeneity and diversity of soil microbiota, the abundance and activity of the AOA and AOB varies, depending on site location, soil type, moisture content, soil pH, nutrient levels, as well as biotic factors such as species–species interactions and viral predation (Erguder et al ., 2009; Pannu et al ., 2019). This complexity makes it challenging to track the relative contributions of each microbial group to ammonia oxidation and N 2 O emissions in different environments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reactive ammonium fertilizer not assimilated by crops or soil microbes can be a major source of N 2 O emissions as a byproduct of ammonia oxidation carried out by ammonia‐oxidizing archaea (AOA) and ammonia‐oxidizing bacteria (AOB) among other abiotic and biotic processes (Sanford et al ., 2012). Due to the vast spatial heterogeneity and diversity of soil microbiota, the abundance and activity of the AOA and AOB varies, depending on site location, soil type, moisture content, soil pH, nutrient levels, as well as biotic factors such as species–species interactions and viral predation (Erguder et al ., 2009; Pannu et al ., 2019). This complexity makes it challenging to track the relative contributions of each microbial group to ammonia oxidation and N 2 O emissions in different environments.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a recent study of the same site as that used in our present study (Prosser, WA, USA) reported an increase in the relative abundance of AOA in intercrop plots (i.e. switchgrass and alfalfa) compared with monocrop fertilized plots, but this increase did not correlate to lower N 2 O emissions (Pannu et al ., 2019), making it challenging to interpret the observed increase in nitrogen and, more specifically, ammonia with relatively low N 2 O emissions from intercrop plots. At another site, intercropping wheat ( Triticum aestium L.) and soybean ( Glycin max L.) were reported to change the dominant species of AOB and increase the expression of nitrogen cycle related functional genes in the rhizosphere (Wallenstein et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these two sources of N 2 O emissions are dominated by microbial activity and largely emitted in pulse events under certain combinations of oxygen and moisture conditions. 89 Binary legume-grass mixtures have been consistently shown to have lower N 2 O emissions than grass-only systems fertilized with mineral N, 80,90,91 suggesting that legume addition to grass monocultures can be an effective means to reduce soil N 2 O emissions. For example, Pannu et al 91 found that intercropping alfalfa into switchgrass did not increase yield as much as did fertilization at 224 kg-N ha À1 year À1 (63% versus 112%); however, the former emitted far less N 2 O per ha of land and thus had 40% lower N 2 O emissions per Mg of biomass produced.…”
mentioning
confidence: 99%
“…89 Binary legume-grass mixtures have been consistently shown to have lower N 2 O emissions than grass-only systems fertilized with mineral N, 80,90,91 suggesting that legume addition to grass monocultures can be an effective means to reduce soil N 2 O emissions. For example, Pannu et al 91 found that intercropping alfalfa into switchgrass did not increase yield as much as did fertilization at 224 kg-N ha À1 year À1 (63% versus 112%); however, the former emitted far less N 2 O per ha of land and thus had 40% lower N 2 O emissions per Mg of biomass produced. Similarly, Johnson and Barbour 80 reported that interseeding legumes into switchgrass and big bluestem led to an average of $30% reduction (yield-scaled) in comparison to a fertilization rate of 112 kg-N ha À1 year À1 .…”
mentioning
confidence: 99%